Mrs. Morris and the Day of the Dead - Wilton, Traci (Wilton, Traci. Salem B&B mystery., 2025)
When Salem B&B owner Charlene Morris investigates the case of a missing woman over a haunted Halloween weekend, she may find herself playing host to a whole new ghost in the newest paranormal cozy mystery from Traci Wilton! Charlene and her spectral companion, Dr. Jack Strathmore, are moved by crystal healer Isabella Perez's story about her missing sister, Marisol, a talented psychic of uncommon natural gifts. The spooky season is the ideal time to contact the departed for some answers; could someone from the other side reveal the truth about her disappearance . . . and the location of the priceless bejeweled statue she took with her? Jack mistrusts Marisol's fiancé, Rico Flores, but any number of suspects had reason to wish Marisol ill, including an embittered stalker obsessed with the talented bruja, a jealous rival witch, and a shady businessman more given to more dirty tricks than treats. Charlene's beau, Detective Sam Holden, is on the case, but unmasking the culprit may require an assist from beyond the grave. Thank goodness it's Halloween, when the veil between the living and the dead is at its thinnest . . .